The impact of pharmaceutical action in improving the quality of life of patients with type II diabetes mellitus: an integrative review (Research, Society and Development, 2023)
Diabetes mellitus is an endocrine-metabolic disease. Patients have high levels of glucose in the blood or hyperglycemia, with a deficient secretion of insulin or a decrease in the action of insulin in the body. Can be caused by the absolute absence of insulin, identified by Diabetes Mellitus type 1 (DM-1) or insulin-dependent, or by insufficient insulin secretion by the pancreas and/or resistance to its action, characterizing Type 2 Diabetes Mellitus (DM-2). The objective of the study was to verify, in previously published works, how the presence of a pharmacist can be important in the treatment and improvement of the quality of life of patients with DM-2. The article was qualitative research of integrative bibliographic review, where the theme was identified, the selection of the research question establishing the inclusion and exclusion criteria. Eleven articles were selected for the study based on the descriptors in Portuguese in the combinations: “pharmaceutical care” and “type 2 diabetes mellitus” and “pharmaceutical care” and “type 2 diabetes mellitus” and “glycemic control” in the SciELO, BVS and Science Direct in Portuguese, English and Spanish over a period of 5 years. It was concluded that the pharmaceutical professional is essential for the health of patients with DM, promoting a reduction in HbA1c levels, a decrease in blood pressure, improvement in triglycerides and greater adherence to drug treatment and economy. Pharmaceutical monitoring in person and by telephone contributed to greater adherence to treatment and improved health as a whole.